Signaling effects of monetary policy - Leonardo Melosi (Federal Reserve Bank of Chicago, 2012)
We develop a DSGE model in which the policy rate signals the central bank.s view about macroeconomic developments to incompletely informed price setters. The model is estimated with likelihood methods on a U.S. data set including the Survey of Professional Forecasters as a measure of price setters.expectations. The signaling effects of monetary policy are found to be empirically important and dampen the effects of monetary disturbances on inflation. While the signaling effects enhance the Federal Reserve.s ability to stabilize the economy in the face of demand shocks, they play a small role in stabilizing the economy after technology shocks.
Keywords: E52; D82; C11; 330; higher-order expectations; imperfect common knowledge; Bayesian econometrics; persistent real effects of nominal shocks